Postoperative quality of life for aesthetic rhinoplasty - Massaki Tani; Igor Giansante; Karina Boaventura Martinelli; Maria Luiza Santos Aiello; José Octávio Gonçalves de Freitas (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: As in many cosmetic procedures, assessment of surgical success in rhinoplasty depends on surgeon satisfaction and, mainly, o n patient satisfaction. Nevertheless, there are few studies on the patient's postsurgical point of view. The aim of this study is to evaluate the degree of satisfaction correlated with quality of life in the late post-operative period of patients undergoing rhinoplasty in the Integrated Plastic Surgery Services of the Ipiranga Hospital. METHODS: Patients undergoing aesthetic rhinoplasty between 2013 and 2014 (n = 60) were selected for the application of two validated questionnaires. All procedures were performed as indicated with the same surgical routine. RESULTS: Questions 2, 5b, 7, 9a, 9d and 11d of the SF -36 questionnaire showed significant to at least one question of the ROE questionnaire (p < 0.05). CONCLUSION: Quality of life is related to the degree of satisfaction in the postoperative of cosmetic rhinoplasty in six issues.